Model of optical microscope with convertible lens - Shakirov, A.L. (Recent Contributions to Physics, 2015)
The aim of the study is to develop an optical microscope model with a convertible lens, consisting of two relatively short-focus lenses. A theoretical model of the microscope including the construction of optical scheme, the course of beams in that and calculation of its linear magnification was developed. The comparison of the suggested model with the model of classical microscope was conducted. Two working dummies were constructed and the method of work was tested. A number of high quality images of specimens and other objects was obtained. The possibility of observing the image directly as well as of steeples changing the scale of the image both for magnifying and diminishing that was demonstrated. This model may be widely used in scientific research.